2014
DOI: 10.1186/1471-2415-14-55
|View full text |Cite
|
Sign up to set email alerts
|

Hyphema is a risk factor for failure of trabeculectomy in neovascular glaucoma: a retrospective analysis

Abstract: BackgroundSeveral retinal ischemic diseases can cause neovascular glaucoma (NVG). Trabeculectomy with mitomycin C (MMC) is a relatively better treatment modality in the management of eyes with NVG than other glaucoma surgeries. The aim of this study was to investigate the factors that may influence the outcome of trabeculectomy with MMC for NVG.MethodsForty-nine NVG eyes from 43 patients (26 males and 17 females) underwent primary trabeculectomy with MMC. The mean follow-up period was 16.8 ± 8.1 months (range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 28 publications
4
48
1
Order By: Relevance
“…A recent report by Nakatake et al . [25] showed that gross hyphema was statistically significantly associated with trabeculectomy failure in NVG patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report by Nakatake et al . [25] showed that gross hyphema was statistically significantly associated with trabeculectomy failure in NVG patients.…”
Section: Discussionmentioning
confidence: 99%
“…Less postoperative hemorrhagic complications and better surgical outcomes were anticipated because of the remarkable rapid and steady suppression of rubeosis after an intraocular injection of bevacizumab [ 17 19 ]. Indeed, postoperative hyphema was significantly less frequent when bevacizumab was used prior to trabeculectomy [ 9 , 11 ] or tube shunt surgery [ 20 – 22 ], although a statistically significant difference vs. control group was not achieved in other reports [ 6 , 10 , 12 , 23 ]. Furthermore, short-term surgical success rate was significantly better in eyes with preoperative bevacizumab injections in trabeculectomy [ 9 , 12 ] and tube shunt surgery [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, short-term surgical success rate was significantly better in eyes with preoperative bevacizumab injections in trabeculectomy [ 9 , 12 ] and tube shunt surgery [ 20 , 22 ]. However, negative results were also reported for trabeculectomy [ 6 , 10 , 11 ] and tube shunt surgery [ 21 , 23 ]. The inconsistent results may stem from differences in the definition of surgical success, patient backgrounds and surgical procedures among different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sisto et al [69] showed 55 % of success rate in a mean follow-up of 35 months with the use of postoperative 5-fluorouracil and 54 % of success rate in a mean follow-up 18 months with intraoperative mitomycin C. Still, compared to other types of glaucoma, NVG is a known risk factor for surgical failure [70]. Moreover, it has been suggested that a postoperative hyphema, a common complication in patients with NVG, may be associated with higher rates of trabeculectomy failure in NVG [71]. …”
Section: Introductionmentioning
confidence: 99%